High-resistance connection diagnosis in five-phase pmsms based on the method of magnetic field pendulous oscillation and symmetrical components - Hao, Chen (2021)
An on-line approach for diagnosing high-resistance connection (HRC) faults in five-phase permanent magnet synchronous motor (PMSM) drives is presented in this paper. The development of this approach is based on a so-called magnetic field pendulous oscillation (MFPO) technique and symmetrical components method. Under HRC fault condition, a 'swing-like MFPO phenomenon is observed compared to the healthy condition. Furthermore, with the extracted current features in symmetrical components domain, different HRC fault types are successfully identified and distinguished. These fault types include (i) single-phase faults, e.g., HRC fault in phase-A, (ii) two-phase non-adjacent faults, e.g., HRC fault in phase-A&C, and (iii) two-phase adjacent faults, e.g., HRC fault in phase-A&B. Meanwhile, the localization of the faulty phase/phases is also accomplished, and the fault severity is estimated. In this approach, only sensing of the phase currents is needed. Hence, the implementation cost is very low, since the sensory data of the currents are typically already available in the closed-loop vector-controlled drives for control purpose and no additional sensors or related signal conditioning circuits are required. The effectiveness of the presented diagnostic approach is verified by simulations and experimental results.